2007
DOI: 10.1080/09537100701194871
|View full text |Cite
|
Sign up to set email alerts
|

Depression of platelet counts in apparently healthy children with asymptomatic malaria infection in a Nigerian metropolitan city

Abstract: Asymptomatic malaria infection is a common feature of malaria endemic regions in the tropics. In this prospective cross sectional survey, involving 240 children aged 1 to 8 years (Boys = 117, Girls = 123; Ratio 1:1.05), the median platelet count was 115 x 10(9)/L (IQR 97.5-190). Thirty-three out of 240 (13.75%) of the children had thrombocytopenia (platelet count < 100 x 10(9)/L). Malaria parasite was found to exert significant reduction in platelet count. This reduction was more pronounced in children under 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…This is in accordance with a previous observation, where it was shown that the pattern of thrombocytopenia and parasitemia did not have a linear relationship among malaria-infected Nigerian children [14]. However, among Papuan adults, platelet counts were negatively correlated with the level P. falciparum parasitemia [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with a previous observation, where it was shown that the pattern of thrombocytopenia and parasitemia did not have a linear relationship among malaria-infected Nigerian children [14]. However, among Papuan adults, platelet counts were negatively correlated with the level P. falciparum parasitemia [12].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, platelet count is being evaluated as a predictor and prognostic feature of malaria infection [11]. However, most research on thrombocytopenia and malaria is focused on non-pregnant populations including adults and children with symptomatic and asymptomatic P. falciparum infections [12-14]. There are few published data on platelets and P. falciparum infection during pregnancy [15].…”
Section: Introductionmentioning
confidence: 99%
“…The comparison analysis indicated that the extracts significantly prevented weight loss in dose dependent manner compared to the negative control. The results showed that the physical status of the rats were better and this may be due to ameliorating effect of the plant extracts on acute fluid loss, proteolysis and lipolysis which are usually associated with weight loss in malaria infection (Jeremiah and Uko, 2007). Interaction study (ESJL and ESJR) on NK67 Chloroquine resistance P. berghei infected mice showed additive activities.…”
Section: Effect Of Extracts On Hematological Parameters and Weightmentioning
confidence: 80%
“…Similarly, a cross-sectional study on Nigerian children with asymptomatic malaria showed that malaria parasites cause a significant reduction in platelet counts with more pronounced reduction in children under 5 years of age [73]. Therefore, thrombocytopenia is not only a feature exhibited by acute malaria, but also a potentially useful indicator for monitoring asymptomatic children in high transmission areas.…”
Section: Role Of the Malaria Parasite In Asymptomatic Malariamentioning
confidence: 99%